2019
DOI: 10.1161/circep.119.007415
|View full text |Cite
|
Sign up to set email alerts
|

Deep Negative Deflection in Unipolar His-Bundle Electrogram as a Predictor of Excellent His-Bundle Pacing Threshold Postimplant

Abstract: Background: His-bundle pacing (HBP) is a physiological form of pacing. Although high capture thresholds are common, few predictors of low HBP threshold have been determined. We aimed to identify electrophysiological predictors. Methods: Fifty-one patients (53% with atrioventricular block) underwent HBP for bradycardia with an intrinsic QRS duration of <120 ms. Attempts to anchor the HBP lead were guided by unipolar His-bundle electrograms (HB EGMs) r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 17 publications
0
16
0
1
Order By: Relevance
“…LBB COI reflects the anatomic location of the 3830 lead tip in the LBB region, presumably because of focally damaged cell membranes consequent to the trauma of electrode pressure against main conduction branch. LBB COI was observed in 77 out of 115 (67.0%) patients with an LBB potential, a rate higher than reported at the His bundle COI (37%‐45%) 3,4 . Compared with anatomical characteristics of His bundle which is in a small and often insulated region of the atrioventricular junction, and often buried deep within the endocardium, the proximal left bundle branches fan out through the LV septum and forms a wider target 12 .…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…LBB COI reflects the anatomic location of the 3830 lead tip in the LBB region, presumably because of focally damaged cell membranes consequent to the trauma of electrode pressure against main conduction branch. LBB COI was observed in 77 out of 115 (67.0%) patients with an LBB potential, a rate higher than reported at the His bundle COI (37%‐45%) 3,4 . Compared with anatomical characteristics of His bundle which is in a small and often insulated region of the atrioventricular junction, and often buried deep within the endocardium, the proximal left bundle branches fan out through the LV septum and forms a wider target 12 .…”
Section: Discussionmentioning
confidence: 85%
“…Fixation of leads into myocardial tissue during cardiac device implantation results in acute tissue injury also known as current of injury (COI) and is recognized by an elevation of the ST‐segment compared with baseline and an increase in the duration of the intracardiac electrogram (EGM) 1 . Several studies have demonstrated that the presence of a COI is associated with better acute performance and long‐term stability with active fixation leads 1–6 . Vijayaraman et al 3 reported the presence of His bundle COI with leads implanted at the His bundle.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Japan, HBP was introduced in 2017, and the number of HBP implantations performed for conduction diseases has been gradually increasing. There were several reports of unique observations in patients who received HBP, and studies with small sample sizes in single centers in Japan . However, the long‐term performance, efficacy, and safety of HBP in Japanese patients are unknown.…”
Section: Discussionmentioning
confidence: 99%